Okara na alimentação de frangos de corte na fase inicial e de crescimento - Diaz Vargas, Mayra (2013)
Three experiments were carried out to determine the chemical composition, energetic values of okara and the inclusion effect of this residue concerning zootechnical parameters, intestinal morphology and meat quality of broilers chickens. Experiment I - 168 21-day old males broilers were distributed in a completely randomized design with three treatments, four replicates and six birds per experimental unit. To determine the energetic value and chemical composition of okara, the method used was the total excreta collection, using the iron oxide as a chemical marker. The treatments were a reference animal feed and two levels of okara replacement of 20% and 40%. The value for apparent metabolizable energy (AME), expressed in kcal/kg as fed basis, and the coefficient of metabolizability (CAME), in percentage, were respectively 2.972 and 60,72%. Experiment II ? 840 one-day old males chicks were distributed in a completely randomized design with five treatments, six replicates and 28 chicks per experimental unit. The treatments consisted of diets containing 0; 2.5; 5.0; 7.5 and 10% of okara. The experimental diets were administered from the 1st to the 21st days of life, after this period a diet based on corn and soybean meal was provided. The supplementation of okara decreases linearly the body weight gain and feed intake, without affecting the feed conversion, during the period from the 1 to the 21st days of life. Under a control diet (0% of okara) from the 21st to the 42nd days of life it was noticed that the birds recovery the performance parameters at the end of the experimental period. Although no improvements occurred on carcass, breast and leg yield, a quadratic effect was observed on wing yield, with higher yield at the level of 6.89% of okara. The parameters of intestinal morphology of animals fed with the level close to 7.5% of inclusion of okara were lower, so that compromises the development of the intestinal morphology. According to the economic evaluation of this residue it was observed that on the initial phase the level of 10.00% of inclusion of okara presented the best economic parameters. Experiment III - 575 21 day-old males broilers were distributed in a completely randomized design with five treatments, five replicates and 23 chicks per experimental unit. The experimental diets corresponded to the same used in the Experiment II. The experimental diets were administered from the 21st to the 42st days of life, before that period a diet based on corn and soybean meal was provided. There was no difference between the different levels of inclusion for the parameters of performance, carcass yield, meat quality, bone parameters and serum levels of cholesterol, calcium and phosphorus at 42 days old. The inclusion of 10% of okara in broilers feed improved the antioxidant activity in meat, decreasing the lipid oxidation and increasing the expired date of the product. The levels of triglycerides show a quadratic behavior with the lowest level stated with 6.53% of okara. The economic evaluation of the use of this residue, based on performance parameters indicated the inclusion of 5.0% of okara as the one that show the best parameters relative to the cost of the animal feed, average gross income and gross margin. According to the results, okara can be included in diets for broiler chickens from 21 to 42 days old until the level of 10% in the diet, without affecting the performance, yield and bone parameters and the quality of the meat. Na alimentação de frangos de corte na fase inicial (1 a 21 dias de idade) e na fase de crescimento (22 a 42 dias de idade) okara pode ser utilizado em até 10% de inclusão na ração sem prejuízo no desempenho, rendimento de carcaça, parâmetros sanguíneos e com melhores índices econômicos sendo economicamente viável na fase inicial sua utilização até 10% e na fase de crescimento em até 5%.